UNUSUAL CASE OF STELLATE NONHEREDITARY IDIOPATHIC FOVEOMACULAR RETINOSCHISIS. (2017) - Dolz-Marco, Rosa; Kato, Kenneth; Freund, K. Bailey; Yannuzzi, Lawrence A.
Abstract : Purpose: To report a case of unilateral stellate nonhereditary idiopathic foveomacular retinoschisis (SNIFR) in a young male showing structural changes induced by a Valsalva maneuver. Methods: Case report of a 26-year-old oboist with SNIFR, including multimodal imaging. Eye-tracked spectral-domain optical coherence tomography (SD-OCT) was used to compare the retinal architecture at rest and during a Valsalva maneuver. Results: Spectral-domain optical coherence tomography showed macular and peripapillary retinoschisis with no signs of pathologic myopia, optic pit, or vitreoretinal traction. A full-field electroretinogram showed supranormal responses in the eye studied. Magnetic resonance imaging of the brain showed no abnormalities. Eye-tracked SD-OCT scans showed an increase in retinal thickness reaching 28 microns superior to the disc during an induced Valsalva maneuver. Conclusion: Stellate nonhereditary idiopathic foveomacular retinoschisis is a diagnosis made when other known causes of retinoschisis have been excluded. In this patient with unilateral SNIFR, an increase in retinal thickness during a Valsalva maneuver was demonstrated. Further study would be needed to determine the mechanism producing this change and to assess its potential influence on visual prognosis. Abstract : The authors present an unsusual case of unilateral stellate nonhereditary idiopathic foveomacular retinoschisis in a young oboist showing mild changes in retinal thickness associated with an induced Valsalva maneuver.